Stone in Metal Ages : proceedings of the XVIII UISPP World Congress (4-9 June 2018,. - Manclossi, Francesca; Marchand, Florine; Boutoille, Linda; Cousseran-Néré, Sylvie (Archaeopress Archaeology, 2020)
Papers from Session XXXIV-6 of the XVIII UISPP World Congress 2018 were divided into two parts, the first dealing with lithic technology, use-wear analyses and the relation between the decline of stone and the development of metallurgy while the second focused on stone tools used for metallurgy. This publication combines these two parts.